2005
DOI: 10.1161/01.res.0000172556.05576.4c
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1–Induced Arrhythmogenic Ca 2+ Signaling Is Abolished in Atrial Myocytes of Inositol-1,4,5-Trisphosphate(IP 3 )–Receptor Type 2–Deficient Mice

Abstract: Abstract-Recent studies have suggested that inositol-1,4,5-trisphosphate-receptor (IP 3 R)-mediated Ca 2ϩ release plays an important role in the modulation of excitation-contraction coupling (ECC) in atrial tissue and the generation of arrhythmias, specifically chronic atrial fibrillation (AF). IP 3 R type-2 (IP 3 R2) is the predominant IP 3 R isoform expressed in atrial myocytes. To determine the role of IP 3 R2 in atrial arrhythmogenesis and ECC, we generated IP 3 R2-deficient mice. Our results revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
347
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 299 publications
(360 citation statements)
references
References 41 publications
12
347
1
Order By: Relevance
“…It should be noted that mice deficient in cardiac expression of type 2 IP 3 Rs are viable and do not have any apparent cardiac defects [17]. Furthermore, complete single deletion of type 1, type 2 or type 3 IP 3 Rs in mice, or combined knockout of types 2 and 3 IP 3 Rs, does not prevent the murine heart (or whole animal) from developing [110,111].…”
Section: Ip 3 Signaling In Cardiac Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…It should be noted that mice deficient in cardiac expression of type 2 IP 3 Rs are viable and do not have any apparent cardiac defects [17]. Furthermore, complete single deletion of type 1, type 2 or type 3 IP 3 Rs in mice, or combined knockout of types 2 and 3 IP 3 Rs, does not prevent the murine heart (or whole animal) from developing [110,111].…”
Section: Ip 3 Signaling In Cardiac Developmentmentioning
confidence: 99%
“…It has been proposed that type 1 IP 3 Rs are dominant in human atrial and rat Purkinje myocytes [15,16], whereas atrial and ventricular myocytes from most other animal species express predominantly type 2 IP 3 R and, to a lesser extent, type 3 IP 3 R (e.g. [17,18]). Overall, the majority of studies have concluded that the most prevalent IP 3 R isoform within contractile cardiomyocytes is type 2 (see Table 1).…”
Section: The Abc Of Ip 3 : Where Does It Come From and Where Does It Go?mentioning
confidence: 99%
See 3 more Smart Citations